The Protection of Personal Data Amid Digital Transformation and Saudi Vision 2030 - Lana Saad Al-Johany (International Journal of Law Research and Studies, 2025)
The study addressed the legal protection of individuals’ personal data amid the digital transformation taking place in the Kingdom of Saudi Arabia. The Saudi legislator has given significant attention to safeguarding such data through the enactment of the Personal Data Protection Law and related regulations. Nevertheless, the concept of data protection in the current era may still lack clarity, particularly in view of the violations that may occur. The central problem of the study lies in identifying the nature of the legal protection established by the Saudi legal system for personal data, the key safeguards that ensure such protection, as well as clarifying the rights of data subjects and the obligations imposed on entities collecting or processing individuals' personal data.The study concludes with several findings, the most significant of which is that the Saudi Personal Data Protection Law does not limit the forms of personal data covered by protection; rather, it broadens the scope to ensure legal protection for any new forms of personal data that may emerge amid rapid digital development, so long as the data retain a personal character. The study also concluded with several recommendations, most notably the need to specify a time within which personal data must be destroyed once their intended purpose has been fulfilled, in addition to tightening oversight of entities engaged in collecting individuals' personal data.
Keywords: Personal Data; Saudi Legal System; Digital Transformation; Privacy Protection; Individual Rights